Improve your writing - Fry, Ronald W. (Franklin Lakes, NJ : Career Press, 1996)
Offers advice on writing research papers, discussing the different elements that make up a research paper, how to select a topic, and how to use the library, and covering the actual writing, documentation, editing, and proofreading.
Includes index.
Young Adult
Keywords: Report writing -- Handbooks, manuals, etc; Research -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc; Research -- Handbooks, manuals, etc